The Influence Of Mental Toughness on The Achievement Of Professional Athletes - Hasmyati Hasmyati; Nur Indah Atifah Anwar; Andi Atssam Mappanyukki; Alimin Hamzah (UNIVERSITAS NEGERI MAKASSAR, 2022)
This study aims to examine the relationship between mental toughness and athlete achievement. The research method used in this study is correlation research with a descriptive research design. This research was conducted in the city of Makassar with the population in this study being PORPROV 2022 athletes in Sinjai Regency. For the sampling technique, we used convenience sampling by giving freedom to the sample over availability to be the research sample in this study. Through this sampling, the number of samples in this study amounted to 38 athletes. The instrument used in this study was mental toughness (AfMTI) to measure the mental toughness of athletes, and an achievement instrument to take the number of medals with the top three rankings obtained by athletes. The results showed that there was a significant relationship between mental toughness and professional athlete achievement.